Source Code Generator Based on Dynamic Frames - Radošević, Danijel; Magdalenic, Ivan (Journal of Information and Organizational Sciences, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false HR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This paper presents the model of source code generator based on dynamic frames. The model is named as the SCT model because if its three basic components: Specification (S), which describes the application characteristics, Configuration (C), which describes the rules for building applications, and Templates (T), which refer to application building blocks. The process of code generation dynamically creates XML frames containing all building elements (S, C ant T) until final code is produced. This approach is compared to existing XVCL frames based model for source code generating. The SCT model is described by both XML syntax and the appropriate graphical elements. The SCT model is aimed to build complete applications, not just skeletons. The main advantages of the presented model are its textual and graphic description, a fully configurable generator, and the reduced overhead of the generated source code. The presented SCT model is shown on development of web application example in order to demonstrate its features and justify our design choices.